2013
DOI: 10.1111/1750-3841.12053
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Bacteriocin KU24 Produced by Lactococcus lactis KU24 against Methicillin‐Resistant Staphylococcus aureus

Abstract: Bacteriocin KU24 produced by Lactococcus lactis KU24 exhibited an inhibitory effect against methicillin-resistant Staphylococcus aureus (MRSA). Bacteriocin KU24 was inactivated by protease XIV, showing that it has a proteinaceous nature on S. aureus ATCC 33591. Also, bacteriocin KU24 exhibited a strong heat stability (121 °C for 15 min) and pH stability (pH 3 to 9). The mode of inhibition was determined for S. aureus ATCC 33591 by treatment of 0, 250, and 500 AU/mL of bacteriocin KU24. S. aureus ATCC 33591 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…These results suggested that AI-hemocidin 2 is capable of destroying cellular integrity and inducing significant deformation in cellular morphology. The cell surface changes induced by AI-hemocidin 2 were similar to those previously reported [ 31 , 51 ]. Peptides interact with the cellular membrane via binding to negatively charged constituents on the outer membrane, such as lipopolysaccharide (LPS), which is followed by membrane destabilization [ 52 ].…”
Section: Resultssupporting
confidence: 89%
“…These results suggested that AI-hemocidin 2 is capable of destroying cellular integrity and inducing significant deformation in cellular morphology. The cell surface changes induced by AI-hemocidin 2 were similar to those previously reported [ 31 , 51 ]. Peptides interact with the cellular membrane via binding to negatively charged constituents on the outer membrane, such as lipopolysaccharide (LPS), which is followed by membrane destabilization [ 52 ].…”
Section: Resultssupporting
confidence: 89%
“…Treatment with LAB bacteriocins is an effective and safe way to inhibit S. aureus growth in food. Many researchers have shown that LAB bacteriocins have anti-MRSA ability [ 11 , 24 , 25 ]. However, only a few studies have been performed to investigate the LAB bacteriocins against other drug-resistant S. aureus such as anticiprofloxacin, anticefoxitin, and antigentamicin [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria produce antimicrobial compounds like organic acids, diacetyl, hydrogen peroxide, and proteinaceous bacteriocins ( Lee et al ., 2013 ). Bacteriocins are antimicrobial peptides or proteins produced by mainly lactic acid bacteria; these compounds are small and ribosomally synthesized.…”
Section: Natural Preservatives From Microorganismsmentioning
confidence: 99%